The adnAB Locus, Encoding a Putative Helicase-Nuclease Activity, Is Essential in Streptomyces - Zhang, Lingli (American Society for Microbiology, 2014)
Homologous recombination is a crucial mechanism that repairs a wide range of DNA lesions, including the most deleterious ones, double-strand breaks (DSBs). This multistep process is initiated by the resection of the broken DNA ends by a multisubunit helicase-nuclease complex exemplified by Escherichia coli RecBCD, Bacillus subtilis AddAB, and newly discovered Mycobacterium tuberculosis AdnAB. Here we show that in Streptomyces, neither recBCD nor addAB homologues could be detected. The only putative helicase-nuclease-encoding genes identified were homologous to M. tuberculosis adnAB genes. These genes are conserved as a single copy in all sequenced genomes of Streptomyces. The disruption of adnAB in Streptomyces ambofaciens and Streptomyces coelicolor could not be achieved unless an ectopic copy was provided, indicating that adnAB is essential for growth. Both adnA and adnB genes were shown to be inducible in response to DNA damage (mitomycin C) and to be independently transcribed. Introduction of S. ambofaciens adnAB genes in an E. coli recB mutant restored viability and resistance to UV light, suggesting that Streptomyces AdnAB could be a functional homologue of RecBCD and be involved in DNA damage resistance.